2000
DOI: 10.1002/1097-4679(200010)56:10<1239::aid-jclp2>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and managing violence risk in outpatient settings

Abstract: Psychologists and other mental health professionals practicing in essentially all clinical settings are called on to assess and manage clients who may pose a risk of violence to third parties. Over the past 25 years much has been learned about the relationship between violence and mental disorder, and about assessing violence risk. In this article risk factors for violence among persons with mental disorder are reviewed, clinical assessment strategies are discussed, and a model for thinking about treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 64 publications
(87 reference statements)
1
105
0
5
Order By: Relevance
“…In fact, some literature contends that, at best, clinical judgments made with unstructured prediction methods have a ''modest, better-than-chance level of accuracy'' (Mossman, 1994, p. 790). More recent reviews, however, indicate that accurate predictions of violence are indeed attainable (Borum, 1996;Douglas & Webster, 1999;Otto, 2000). For example, a number of studies have supported the predictive validity of adult risk assessment instruments that follow the actuarial and structured professional judgment model (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some literature contends that, at best, clinical judgments made with unstructured prediction methods have a ''modest, better-than-chance level of accuracy'' (Mossman, 1994, p. 790). More recent reviews, however, indicate that accurate predictions of violence are indeed attainable (Borum, 1996;Douglas & Webster, 1999;Otto, 2000). For example, a number of studies have supported the predictive validity of adult risk assessment instruments that follow the actuarial and structured professional judgment model (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of tools that use this approach including the HCR-20. This method of risk assessment can provide some predictive value and be more reliable than unstructured clinical judgement (Otto, 2000). Commentators have suggested that clinical judgement within a structured context can contribute significantly to risk assessment for violence by, for instance, guiding risk management strategies (Douglas et al, 2003).…”
Section: Risk Assessment Methodsmentioning
confidence: 99%
“…Als Indikatoren einer erhöhten Wahrscheinlichkeit für gewalttätiges Verhalten gelten nicht nur klinische, sondern auch soziale Faktoren wie geringe soziale Unterstützung, Schwierigkeiten in sozialen Beziehungen, erlebtes Mobbing, Gewalt im sozialen Umfeld oder früheres gewalttätiges Verhalten (Dressing u. MeyerLindenberg 2010;Otto 2000). Bei den klinischen Faktoren erhöhen gesteigerte Impulsivität, geringe affektive Regulationsfähigkeit sowie paranoide Gedanken das Risiko für aggressives Verhalten, ebenso damit verbunden das Vorliegen von Abhängigkeitserkrankungen, Schizophrenien und einigen Persönlichkeitsstörun-gen, insbesondere Borderline-, narzisstische und antisoziale Persönlichkeits-störungen (Johnson et al 2000;Nestor 2002).…”
Section: Soziale Und Klinische Faktorenunclassified